Comparison Of Lactobacillus Plantarum, Lactobacillus Mucosae And Lactobacillus Farciminis Bacteria Between Polycystic Ovary Syndrome And Non Polycystic Ovary Syndrome Students At Medical Faculty Of Andalas University - Putri, Mentari Faisal; Haviz Yuad; Andani Eka Putra (Andalas Obstetrics And Gynecology Journal, 2024)
Background: Polycystic Ovary Syndrome (PCOS) is a disorder characterized by hyperandrogenism, ovulatory dysfunction, and morphological features of polycystic ovaries. It is associated with insulin resistance and hyperinsulinemia. Gut microbial dysbiosis plays a role in PCOS, which is associated with insulin resistance, hyperandrogenism, chronic inflammation, and metabolic syndrome. PCOS treatment with Probiotics maintains the stability and diversity of the gut microbiome. Objective: To determine the comparison of Lactobacillus plantarum, Lactobacillus mucosae, and Lactobacillus farciminis Bacteria Between Polycystic Ovary Syndrome and Non Polycystic Ovary Syndrome Students at the Medical Faculty of Andalas University. Method: This research was an analytic observational study using a cross-sectional method conducted on female students with Polycystic Ovary Syndrome and Non-Polycystic Ovary Syndrome at the Medical Faculty of Andalas University. Results: Bivariate analysis of microbiota comparison of female students with PCOS and without PCOS, Mann-Whitney Test on L.mucosae (p=0.774), while Independent T-Test analysis on L.farciminis (p=0.006). Conclusion: There is a decrease in microbiota L. Mucosae in female students with PCOS, but there is no significant difference. There is a significant comparison in the number of microbiota L.farciminis in female students with and without PCOS at FK Unand.